Alevilikte hak, Muhammed, Ali inancı - Yakar, Sümeyra (My University, 2011)
Alevilik, Hak, Muhammed, Ali ÖZET Alevilik eski Türk inançlarındaki bazı unsurları İslam inançlarıyla birleştiren grubun bugünkü ismidir. Alevilik’te çok önemli bir etkisi olan Allah-Muhammed-Ali anlayışı bu sosyal olgunun temelidir. Bu yüzden bu konu Alevilik’in kültürel kaynakları olan Menakıbnameler, temel erkân kitabı Buyruk ve deyişlere göre açıklanmaya çalışılır. Tez üç ana bölüm ve bir sonuç kısmına sahiptir. İlk bölüm Alevi gelenekte Allah inancıdır. Allah inancı ve bu inancın kültürel arka planı açıklanmış, daha sonra Allah inancındaki vahdet-i vücut anlayışı, Allah-Ali ilişkisi, devir ve tecelli inancından bahsedilmiştir. Bundan sonra Allah’ın nitelikleri ve sevgisine değinilmiştir. İkinci bölüm Alevi kaynaklarındaki peygamber inancıdır. Alevi anlayışında genel olarak peygamberlik inancı özelde ise Hz. Muhammed inancının analizi yapılmıştır. Muhammed anlayışı hakkında da üç görüş vardır: biricisi, Muhammed-Ali tasavvuru; ikincisi, Nur-ı Muhammedi veya Muhammed-Ali nuru; üçüncüsü, Lahmuke Lahmi anlayışıdır. Bunlardan sonra Muhammed’in nitelikleri ve sevgisinden bahsedilmiştir. Üçüncü bölüm Ali anlayışıdır. Hz. Ali Alevilik’teki özel konumu sebebiyle tarihi kişiliğinden koparılarak tamamıyla farklı bir kimliğe büründürülmüştür. Bu sebeple ilk olarak Ali’nin önemi, hayatı ve kişiliğinden bahsedilip daha sonra Ali anlayışı hakkında dört görüşe yer verilmiştir. Bunlar Ali’nin ulûhiyeti, Ali’nin velayeti, Ali’nin Muhammed’le özdeşliği ve Ali- Hacı Bektaş-ı Veli ilişkisidir. Bölüm Ali’nin özellikleri ve sevgisinden bahsederek sona ermiştir. Alawism, God, Prophet, Ali

Alavi is the current name of a group combining some elements of the old beliefs of Turks with the İslamic beliefs. The perception of God, Prophet and Ali which is significant effect in the Alevism is the foundation of this social phenomenon. Therefore, this topic attempt to explain the cultural sources of Alevism, Manaqibs with the essential book called Buyruk and folk poems. This thesis has got three main sections and a conclusion part. The first chapter is the belief of God in Alavi Tradition. The belief of God and the cultural background of this belief are described. And then, the faith of God is displayed in three categories: First, the belief of “wahdat al-wujud”; second, the perception that relation between God and Ali; third, the belief of circulation and manifestation about God. After that, from God’s attributes and love are discussed. The second section is the belief of prophet in the sources of Alevism. A general analyisis of the faith for prophethood is made and a particular analyisis of the faith for Muhammed is made in Alevi phlosophy. The perception of Muhammed is also denominated in three categories; first, the imagination of Muhammed-Ali; second, the imagining that Nur-ı Muhammedi and the light of Ali, third, the understanding of Lahmike Lahmi. Finally, Muhammed’s attributes and love are explained. The third division is the perception of Ali. This perception has been created in a particular form in Alevism, despite the perception of him being understood differently due to his special status in the history of İslamic beliefs, mysticism and politics. Hence, the importance of Ali, his life and personality are discussed. Furthermore, the perceptions of Ali are displayed in four categories; first, the perception that gives the status of divinity to Ali; second, the belief that regards him as the greatest Saint; third, the perception that identifies him with the prophet Muhammed; fourth, perception that identifies him with Hacı Bektaş-ı Veli. Chapter ends by describing Ali’s features and the love of him. In the conclusion part, an assesment is made about the whole work by writer.
Keywords: Alevilik; İslam Mezhepleri